The Relation Between Human Values and Perceived Situation Characteristics in Everyday Life - Kesberg, Rebekka; Keller, Johannes (Frontiers in Psychology, 2018)
Values refer to abstract beliefs which serve as guidelines in peoples’ life and affect the way people and events are evaluated. Simultaneously, unlike attitudes, values transcend specific actions, and situations. While recent research showed that values are related to the attention and interpretation of situational information in standardized laboratory settings, up to date hardly any empirical work investigated how values relate to situation perception in daily life. In our study, we assessed the relation between the endorsement of human values and situation characteristics (i.e., the 8 DIAMONDS). Using the Day Reconstruction Method in two samples (German and US-American), we found that especially variance in the experience of negatively connoted situation characteristics were due to individual differences. Power was related to experiencing more deceptive situations, while the reversed pattern emerged for universalism and benevolence. Tradition was related to experiencing more aversive situations while self-direction was related to experiencing less situations high in adversity. Although, our results might provide some initial evidence for a relation between personal values and subjective situations experiences in everyday life, no clear pattern emerged and further investigation of the relation is necessary.